Teacher Moments: A Digital Simulation for Preservice Teachers to Approximate Parent–Teacher Conversations. Issue 3 (3rd July 2019) - Thompson, Meredith; Owho-Ovuakporie, Kesiena; Robinson, Kevin; Kim, Yoon Jeon; Slama, Rachel; Reich, Justin
Abstract: Interactive simulations allow preservice teachers to connect education theory and pedagogy in scaffolded environments. We created digital simulations with scenarios from in-person simulations and used them to prepare novice teachers for conversations with parents. Using a design-based approach we implemented the simulations in an education class, gathered data through surveys and observations, and incorporated feedback into subsequent designs. Novice teachers perceived the simulation as authentic and practiced maintaining composure and articulating pedagogical approaches. Recordings of novice teachers' responses produced by the simulation enabled self-reflection and peer and instructor feedback. Results suggest that these digital simulations hold promise as low-cost, flexible tools for novice teachers to engage in targeted practice in a low-stakes setting.